Improving Children's Language Skills Learning through Storytelling Method Using the Story Tree Media in Group B at Al Atfal Qusqazah Inclusive Kindergarten Medan - Rita Nofianti; Nanda Rahayu Agustia; Putri Aulia (International Journal of Society and Law, 2024)
The background of this study is the children's limited vocabulary, their inability to construct sentences from existing pictures, and their struggle to express opinions and thoughts on various topics. The objective of this research is to describe how children's language skills can be improved through the storytelling method using the story tree media for Group B at Al Atfal Qusqazah Inclusive Kindergarten in Medan. This study employs a classroom action research method. The findings indicate that the improvements made to language skills using the storytelling method through the story tree in Group B at Al Atfal Qusqazah Inclusive Kindergarten resulted in enhanced language abilities among the children. This is evident from the changes observed in Cycle 1, where 2 children were still "Not Yet Developing" (BB) and 2 children were "Developing as Expected" (BSH). After Cycle 2, only 1 child remained at the BB level, while 2 children had achieved the "Very Well Developed" (BSB) rating.